Impact of Lymph Node Ratio and Adjuvant Therapy in Node-Positive Endometrioid Endometrial Cancer. Issue 8 (October 2015) - Fleming, Nicole D.; Soliman, Pamela T.; Westin, Shannon N.; Reis, Ricardo dos; Munsell, Mark; Klopp, Ann H.; Frumovitz, Michael; Nick, Alpa M.; Schmeler, Kathleen; Ramirez, Pedro T.
<x xml:space="preserve">Abstract</x> Objectives To determine if the ratio of positive to negative lymph nodes, or lymph node ratio (LNR), is a prognostic variable in patients with node-positive endometrial cancer and the impact of adjuvant therapy on survival. Methods After institutional review board approval, a retrospective review of patients diagnosed as having stage IIIC endometrioid or mixed endometrioid endometrial cancer at a single institution from January 2000 through October 2011 was performed. Clinicopathologic and adjuvant treatment data were collected. Univariate and multivariate analysis were used to identify prognostic factors for progression-free (PFS) and overall survival. Results One hundred twenty-four patients with stage IIIC1 (n = 64) and IIIC2 (n = 60) endometrial cancer were included in the analysis. Median age was 60 years (range, 25–84 years), and median follow-up was 49.4 months (range, 0.1–301.6 months). Age >70 years was identified as a prognostic factor for worse PFS (P = 0.0002) and overall survival (P = 0.0002) on multivariate analysis. Patients in this cohort receiving any adjuvant radiotherapy showed improved PFS (hazard ratio [HR], 0.34; 95% CI, 0.13–0.90; P = 0.03) compared with those receiving any adjuvant chemotherapy (HR, 2.33; 95% CI, 1.16–4.65; P = 0.02). In a subgroup analysis, patients with at least 10 nodes removed (n = 81) with an LNR greater than 50% had a PFS of 25.2 months compared with 135.6 months with an LNR of 50% or less (HR, 3.87; 95% CI, 1.15–13.04; P = 0.03). Conclusions Lymph node ratio may define a subgroup of stage IIIC endometrial cancers at increased risk for recurrence. Adjuvant radiotherapy was associated with decreased recurrence risk.